Wasp Parasitoid Doryctobracon areolatus (Szépligeti) (Insecta: Hymenoptera: Braconidae) - Charles Stuhl; John Sivinski (EDIS)
Doryctobracon areolatus was introduced into Florida and the Dominican Republic for control of the Caribbean fruit fly and the West Indian fruit fly. In its native habitats, parasitism of fruit flies in certain fruit can reach more than 80%. Mean parasitism of Caribbean fruit fly following original establishment in Florida was around 40%. This 4-page fact sheet was written by Charles Stuhl and John Sivinski, and published by the UF Department of Entomology and Nematology, June 2012.